Genome-Wide Assessment of Runs of Homozygosity and Estimates of Genomic Inbreeding in a Chinese Composite Pig Breed - Xu, Zhong; Mei, Shuqi; Zhou, Jiawei; Zhang, Yu; Qiao, Mu; Sun, Hua; Li, Zipeng; Li, Lianghua; Dong, Binke; Oyelami, Favour Oluwapelumi; Wu, Junjing; Peng, Xianwen (Frontiers in Genetics, 2021)
The primary purpose of the current study was to assess the genetic diversity, runs of homozygosity (ROH) and ROH islands in a Chinese composite pig and explore hotspot regions for traces of selection. First, we estimated the length, number, and frequency of ROH in 262 Xidu black pigs using the Porcine SNP50 BeadChip and compared the estimates of inbreeding coefficients, which were calculated based on ROHs (FROH) and homozygosity (FHOM). Our result shows that a total of 7,248 ROH exceeding 1Mb were detected in 262 pigs. In addition, Sus scrofa chromosome (SSC) 8 and SSC10, respectively, has the highest and lowest chromosome coverage by ROH. These results suggest that inbreeding estimation based on total ROH may be a useful method, especially for crossbreed or composite populations. We also calculated an inbreeding coefficient of 0.077 from the total ROH. Eight ROH islands were found in this study. These ROH islands harbored genes associated with fat deposition, muscular development, reproduction, ear shape, and adaptation, such as TRAF7, IGFBP7, XPO1, SLC26A8, PPARD, and OR1F1. These findings may help to understand the effects of environmental and artificial selection on the genome structure of composite pigs. Our results provide a basis for subsequent genomic selection (GS), and provides a reference for the hybrid utilization of other pig breeds.